2015
DOI: 10.1002/jrs.4843
|View full text |Cite
|
Sign up to set email alerts
|

Reliable determination of the few‐layer graphene oxide thickness using Raman spectroscopy

Abstract: We report on a reference-free Raman spectroscopy method for a precise thickness determination of the multilayered graphene oxide flakes. The method is based on the normalization of the total integral intensity of D and G Raman bands to the integral intensity of the second-order optical phonon peak of the silicon substrate in the Raman spectrum. The normalization provides discrete ratio values corresponding to the number of graphene oxide layers in the respective flakes with the intensity linearly increasing wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 48 publications
5
40
0
Order By: Relevance
“…Similarly to graphene, GO is also highly transparent in the visible range, with the experimentally measured optical contrast of 3.6% on 300 nm SiO2/Si using a 100× objective [38]. Applying the same methodology as for graphene, we found that the stratified heterostructures can also significantly enhance the optical visibility modes are not sensitive to the GO thickness but their intensities increase linearly with the number of layers, which is consistent with previous studies [38,39]. Figure 5e shows the AFM phase image of a monolayer region marked in figure 5b.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly to graphene, GO is also highly transparent in the visible range, with the experimentally measured optical contrast of 3.6% on 300 nm SiO2/Si using a 100× objective [38]. Applying the same methodology as for graphene, we found that the stratified heterostructures can also significantly enhance the optical visibility modes are not sensitive to the GO thickness but their intensities increase linearly with the number of layers, which is consistent with previous studies [38,39]. Figure 5e shows the AFM phase image of a monolayer region marked in figure 5b.…”
Section: Resultssupporting
confidence: 89%
“…figure S4. There is also a variation of monolayer GO ñ and d in literature: n = 1.2 -2.0, κ = 0.1 -0.7, and d = 0.7 -1.5 nm [37][38][39][40], most likely caused by the variability of the oxygen-containing groups of GO.…”
Section: Optical Contrast Simulationmentioning
confidence: 95%
“…Figure (b) presents the Raman map plotting the ratio I D / I G between integrated intensities associated with the disorder‐induced D band and the graphite‐like G band, centred at ∼1340 and ∼1600 cm −1 , respectively (Fig. (d)) . Note that the significant breadth of the D band is directly related to the presence oxygen‐induced defects in G‐O and is fully congruent with the spectral lineshape reported by the G‐O manufacturer (see Section 2.1).…”
Section: Materials Characterization Methodssupporting
confidence: 73%
“…The presence of typical D (Disorder) and G (Graphitic) vibrational bands of GO in the Raman spectrum of c‐TiO 2 /m‐TiO 2 /GO‐Li carried out by focusing the laser beam onto the m‐TiO 2 layer confirms the interpenetration of GO‐Li in the mesoporous layer.…”
Section: Resultsmentioning
confidence: 70%